Evaluation of mobile games using playability heuristics - Soomro, S. (2013)
Touch screen mobile devices have begun to better facilitate different game playing while gaining greater attention among users. 'Playability' is an important element that measures the ease by which games can be played. It is evaluated by two common methods; heuristic evaluation, and playtesting. Several heuristics have been proposed to evaluate playability but users still face playability problems. This paper attempts to evaluate existing mobile games using the heuristic evaluation method in order to examine the extent in which the heuristics support playability. Two sets of existing playability heuristics were used in the study. Six android games of different genres were evaluated by fourteen test participants. The study result reveals that existing playability heuristics lack the capability of identifying playability problems. These problems are usability, mobility, gameplay, and the multiplayer function for touch screen mobile game applications. Thus, there is a need for a new set of playability heuristics that extensively cover all aspects of playability. Â© 2013 Springer International Publishing.